THE INVESTIGATION OF THE CONDITIONS FOR OBTAINING DOUBLE ZINC-CALCIUM PHOSPHATE - Антрапцева, Надежда; Филькин, Игорь (SWorldJournal, 2021)
The conditions of the synthesis of zinc-calcium phosphate by two principal different methods was determined. The phosphate with general formula Zn2Ca(PO4)2·2H2O were synthesized. The reliable experimental given about conditions of the obtaining of the zin